Knowledge and Attitude towards the Use of Contraception among Medical Students in a Private Medical University, Perak, Malaysia - Kyaw Ko Latt; Muhammad Zaid Imran Bin Mohd Johari; Sharifah Nadhirah Binti Syed Azmi; Putri Nurauji Fathini Binti Noorasri; Farisha Sofea Binti Md Roslan (Asian Journal of Medicine & Health Sciences, 2021)
Aims: The study was postulated to assess the level of knowledge and attitude towards the usage of contraception among medical students in University Kuala Lumpur (UniKL) Royal College of Medicine Perak (RCMP). Methods: A total of 241 students had participated through simple random sampling technique in this cross-sectional study. The questionnaire consisted of three components which included demographic characteristics of respondents, knowledge towards contraception and attitude towards contraception. Results: Most of the respondents in this study comprised of Malay (93.36%), female (68.05%) and lived in urban district (70.95%). The study showed that more than half of the students (65.6%, n = 158) had good levels of knowledge while the rest of them (34.3%, n=83) had moderate levels of knowledge and there were no students that had been categorized under poor levels of knowledge towards the usage of contraception. Half of the respondents (51.5%) had moderate attitude towards contraception and 44.8% of the respondents had good attitude towards contraception. However, there were 3.7% of the respondents had poor attitude towards contraception. There were significant associations between gender, place of birth, year of study, and level of knowledge and attitude towards the usage of contraception. Conclusion: This study revealed that the attitude towards contraception among the medical students were not satisfactory and adequate for them to be an excellent health care personnel who were soon to be expected to provide the most reliable knowledge and services on contraception. This deficiency called forth the university on the needs of comprehensive education to be implemented preferably as early as possible for the medical education programmes.